Biodiversity of Marine Interstitial Ciliates in the Intertidal Zone of the White Sea: A Dataset from the Chernaya River Estuary, Kandalaksha Gulf - Xiaolei Li; Anton S. Esaulov; Igor V. Burkovsky; Damir A. Saldaev; Yuri A. Mazei (Diversity, 2023)
(1) Background: An estuary is a zone in which sea and river waters mix. It is a specific area with a very non-stable environment and salinity gradient. However, little is known about the diversity of ciliate communities in estuarine benthic ecosystems in the Arctic. The aim of this paper is to describe the diversity of intertidal ciliates in the Chernaya river estuary (Kandalaksha Gulf, White Sea), which is characterized by a pronounced salinity gradient (0–22‰), on the basis of a recently published dataset. (2) Methods: We conducted our own investigations during the summer periods of 1998–2000. Material was collected at five permanent stations along the salinity gradient (0–22%) of the estuary. For each observation, the coordinates of the sampling sites, the number of individuals observed and the sampling date were recorded. The total effort comprised 35 sampling days, with five sampling sites at each date. (3) Results: The dataset contains 4270 unique occurrences of 119 ciliates taxa (109 species, 8 unidentified species of the genus level and 2 unidentified species on the family level). The total number of specimens represented is 64,475. (4) Conclusions: The largest classes in terms of species diversity are Hypotrichea (27 species), Gymnostomatea (26 species), Oligohymenophorea (17 species) and Karyorelictea (16 species).